Combination therapy of cisplatin and resveratrol to induce cellular aging in gastric cancer cells: Focusing on oxidative stress, and cell cycle arrest - Rahimifard, Mahban; Baeeri, Maryam; Mousavi, Taraneh; Azarnezhad, Asaad; Haghi-Aminjan, Hamed; Abdollahi, Mohammad (Frontiers in Pharmacology, 2023)
Background: As a medical dilemma, gastric cancer will have 7.3 million new cases in 2040. Despite the disease’s high economic and global burden, conventional chemotherapy regimens containing cisplatin have insufficient effectiveness and act non-specifically, leading to several adverse drug reactions To address these issues, the biological efficacy of the cisplatin-resveratrol combination was tested. Methods: To find IC50, gastric adenocarcinoma cells (AGS) were exposed to different concentrations of resveratrol and cisplatin. Anti-cancer and anti-metastatic effects of 100 M resveratrol with concentrations of cisplatin (25, 50, and 100 g/ml) were studied by assessing ß-galactosidase and telomerase activities, senescence and migration gene expression, reactive oxygen species (ROS) level, and cell cycle arrest. Results: Co-administration of cisplatin and resveratrol increased ß-galactosidase activity, ROS level as a key marker of oxidative stress, p53, p38, p16, p21, and MMP-2 gene expression, and induced G0/G1 cell cycle arrest. Additionally, telomerase activity, pro-inflammatory gene expression, and cell invasion were suppressed. The best results were achieved with 100 g/ml cisplatin co-administered with resveratrol. Conclusion: The current study proved the synergistic effect of the cisplatin-resveratrol combination on suppressing metastasis and inducing apoptosis and cell senescence through targeting P38/P53 and P16/P21 pathways. Such promising results warrant translation to animal models and the clinic. This may lead to cost-effective, available, and accessible treatment regimens with targeted action and the fewest ADRs.